Analysis of Cyclamate Content in Unbranded Instant Herbal Medicinal Drink on Market in the City of Pamekasan - Jamila, Nur; Rahman, Alief Putriana; Humaidi, Fauzan (Universitas Airlangga, 2023)
Jamu was one of the traditional medicines because most herbal medicine used natural ingredients or plants. One of the safety of herbal medicine was the absence of abuse such as the addition of artificial sweeteners in the form of cyclamate. Cyclamate was one of the artificial sweeteners that had a sweetness level 30 times higher than natural sweeteners. Excessive use of cyclamate could cause cancer and tumors. The purpose of this study was to determine the presence or absence of cyclamate content and levels in ready-to-drink herbal medicine without a brand sold in the Pamekasan City market. This research was conducted qualitatively with precipitation methods and quantitative with gravimetric methods. From qualitative research, the results of sample A found a white precipitate which indicated a positive sample containing cyclamate. While samples B and C found no deposits indicating that the sample was negative cyclamate. Furthermore, a positive sample was carried out quantitative testing. In determining cyclamate levels, sodium cyclamate levels in sample A were obtained at 4,8047 g/kg, so that the serving rate or per 1 bottle of herbal medicine contains 115,312 g/0,6 kg. This exceeded the threshold determined by BPOM Regulations which is 1,25 g/kg. The conclusion of this study was that 1 out of 3 positive samples contains cyclamate with levels that exceeded the threshold determined by BPOM RI No. 32 of 2019. Keywords: Jamu, Cyclamat, Gravimetry